Improved ethanediol sensing with single Yb ions doped SnO2 nanobelt. Issue 9 (July 2016) - Chen, Weiwu; Liu, Yingkai; Qin, Zhaojun; Wu, Yuemei; Li, Shuanghui; Gong, Nailiang
Abstract: Yb-doped SnO2 nanobelts (Yb–SnO2 NBs) and pure SnO2 nanobelts (SnO2 NBs) are successfully synthesized by thermal evaporation method and their composition and morphology are characterized. The single nanobelt device is fabricated by dual-ion beam deposition system, and the gas sensing performance to ethanediol, methanal, ethanol and acetone is investigated. The results show that the best working temperature of single Yb–SnO2 NB sensor to ethanediol is 190 °C, which is lower than that of pure counterpart and the highest sensitivity is 10.5 to 100 ppm of ethanediol. In addition, it is found that the response/recovery time is short and the sensor exhibits excellent selectivity and stability. The sensing performance of SnO2 NB is actually improved by Yb.